Market Competition and Agency Problem: a Study in Indonesian Manufacturing Companies - Nugroho, Ahmad Cahyo; Stoffers, Jol (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
This research examines the relationship between firm investment and market competition, market position and market position as market leader. This study analyzes agency problems in manufacturing companies’ investment decisions by considering market competition, since market competition is considered as one of essential factor that affect the firm investment. Further, high competition signals company’s increased investment, that leads to business efficiency. Investment decisions are important for companies to survive, and more competitive companies are likely to conduct more risky activities, especially regarding capital expenditures for investments. This study uses the dynamic panel data method, which includes annual financial report of 100 listed manufacturing companies on IDX from 2007 to 2016. The companies were selected after sorting using several criteria, such as completeness of financial report and being registered on IDX during the period. Results suggest that leverage improves management control functions, and competition increases a company’s investments to maintain its position in the market. Competition is not strengthened or weakened by sales growth and there are indications of herding behavior following market leaders.